Analisis Nilai-Nilai Moral pada Novel “Hello” Karya Tere Liye dan Pemanfaatannya Sebagai Bahan Ajar Materi Apresiasi Novel - Fauziyah, Ozah; Subaweh, Ahmad Maskur; Naufal, Muji zain (Universitas Pahlawan Tuanku Tambusai, 2025)
In this era of increasingly rapid development, the influence of social media extends to the educational progress of students, particularly at the high school and equivalent stages. From the start, some of their morals became increasingly declining. Therefore, the author is very interested in providing examples of moral values that have been found in the novel “Hello” Karva Tere Live as reference material for students so they can get a view of what morals they should have. The study utilises a qualitative approach to examine the moral values portrayed in the novel “Hello” by Tere Liye. Data gathering involves using the library method, which includes reading and note-taking. The findings of the study identify four different aspects of moral values depicted in the novel “Hello” by Tere Liye: 1) Connection between individuals 2) Interaction between individuals and God 3) Connection between individuals and others 4) Connection between individuals and the surrounding nature. The four moral values are broken down into 18 (eighteen) moral values as follows: 1) expressing care for others 2) helping others in a mutually beneficial manner 3) negotiating to reach an agreement 4) living in harmony 5) courtesy 6) respect for others 7) keeping promises 8) gratitude 9) problem solver 10) responsibility 11) humility 12) confidence 13) honesty 14) patience 15) patience 16) hardworking 17) reducing waste 18) improving the environment. This research contributes to the preparation of Indonesian language learning modules for XII grade SMA / SMK students who are studying content analysis and novel language.